Penerapan Rehabilitasi Medis Dan Rehabilitasi Sosial Terhadap Korban Penyalahgunaan Narkotika Ditinjau Dari Teori Pemidanaan Relatif - Sutarto Sutarto (Jurnal Penegakan Hukum Indonesia, 2021)
Illegal narcotics has spread to all levels of society. Many people admit that the circulation and abuse of narcotics is a very dangerous threat to the younger generation. The purpose of this research is to study and analyze how the application of rehabilitation in addiction healing for drug addicts, given the difficulty of victims or drug users to be separated from drug dependence individually.  Drug users or addicts on the one hand are perpetrators of criminal acts, but on the other hand are victims (crime with out victims).  Rehabilitation of drug addicts is a form of social protection that integrates drug addicts into social order so that they no longer use drugs. Th e method used in this research is pure l egal research (normative) .  The results of this study are that medical rehabilitation and social rehabilitationboth partially and collectively have a positive effect on victims of narcotics abuse.